2018
DOI: 10.1080/17474124.2018.1424540
|View full text |Cite
|
Sign up to set email alerts
|

Stratified alpha-fetoprotein pattern accurately predicts mortality in patients with acute-on-chronic hepatitis B liver failure

Abstract: Stratified AFP could strengthen the predictive power for short-term survival of patients with ACHBLF. Combining AFP quartiles with low serum sodium and high INR may better predict poor outcome in ACHBLF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…AFP has been widely used as a clinical biomarker of chronic liver diseases and hepatic malignancy . Huang et al suggested that AFP is a marker of liver regeneration, whereby a high AFP was associated with greater hepatocyte regeneration and favorable outcomes in patients with HBV‐ACLF. Kakisaka et al suggested that serum AFP level may reflect the induction of liver progenitor cells in acute liver failure patients, and the persistent induction of liver progenitor cells may be needed for a recovery from liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…AFP has been widely used as a clinical biomarker of chronic liver diseases and hepatic malignancy . Huang et al suggested that AFP is a marker of liver regeneration, whereby a high AFP was associated with greater hepatocyte regeneration and favorable outcomes in patients with HBV‐ACLF. Kakisaka et al suggested that serum AFP level may reflect the induction of liver progenitor cells in acute liver failure patients, and the persistent induction of liver progenitor cells may be needed for a recovery from liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these previous studies, whether Gc and AFP might serve as useful prognostic markers for ALF remains uncertain. Acute on chronic liver failure represents a distinct patient population that has also been evaluated with similar results …”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that AFP could enhance the ability to predict the short-term survival of patients with LF, especially when it is between 76.0 and 252.2 ng/mL. [ 5 ]…”
mentioning
confidence: 99%